Philosophy of behavioral biology - Plaisance, Kathryn S. (Boston studies in the philosophy and history of science ;, 2012)
This volume provides a broad overview of issues in the philosophy of behavioral biology, covering four main themes: genetic, developmental, evolutionary, and neurobiological explanations of behavior. It is both interdisciplinary and empirically informed in its approach, addressing philosophical issues that arise from recent scientific findings in biological research on human and non-human animal behavior. Accordingly, it includes papers by professional philosophers and philosophers of science, as well as practicing scientists. Much of the work in this volume builds on presentations given at the international conference, “Biological Explanations of Behavior: Philosophical Perspectives”, held in 2008 at the Leibniz Universität Hannover in Germany. The volume is intended to be of interest to a broad range of audiences, which includes philosophers (e.g., philosophers of mind, philosophers of biology, and metaethicists), as well as practicing scientists, such as biologists or psychologists whose interests relate to biological explanations of behavior. Contributors - Part I: Introduction - 1. The Philosophy of behavioral biology - 2. Knowledge for what? Monist, pluralist, pragmatist approaches to the sciences of behavior - Part II: Genetic explanations of behavior - 3. Genome wide association studies of behavior are social science - 4. Genetic traits and causal explanation - Part III: Developmental explanations of behavior - 5. From cell-surface receptors to higher learning: a whole world of experience - 6. Re-conceiving nonhuman animal knowledge through contemporary primate cognitive studies - Part IV: Evolutionary explanations of behavior - 7. Evolving the future: sketching a science of intentional change - 8. Human artistic behaviour: adaptation, byproduct, or cultural group selection? - 9. Sensory exploitation: underestimated in the evolution of art as once in sexual selection theory? - 10. Heuristic evolutionary psychology - 11. Evolutionary psychology and the problem of neural plasticity - 12. Free will, compatibilism, and the human nature wars: should we be worried? - 13. Altruistic emotional motivation: an argument in favour of psychological altruism - 14. The neurobiology of altruistic punishment: a moral assessment of its social utility - Part V: Neurobiological explanations of behavior - 15. Behavioral traits, the intentional stance, and biological functions: what neuroscience explains - 16. From reactive to endogenously active dynamical conceptions of the brain.